Implementasi Implementation of the Values of Surah Al-Qamar (QS. 17, 22, 32 and 40) in the Tahfiz Development Program to Increase Motivation to Memorize for Basic Non-Pesantren Students - Hanum, Marsella Tria Amanda; Isnaeni, Ahmad; Irawan, Yoga (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2025)
This study aims to describe the implementation of the values in Surah al-Qamar, verses 17, 22, 32, and 40, to enhance motivation to memorize the Qur’an among non-pesantren basic-level students at Ma’had al-Jāmi’ah, UIN Raden Intan Lampung. The research employs a qualitative descriptive approach, using phenomenological methods and the Living Qur’an study framework. Data collection techniques include participatory observation, in-depth interviews, and documentation. The findings indicate that the students have gradually internalized the values of Surah al-Qamar through mentoring activities, memorization submissions, and the cultivation of a supportive environment. Although the implementation of these verses is still in its early stages, students have shown increased motivation, perseverance, and self-confidence in their memorization journey. These findings suggest that strengthening Qur’anic values can be an effective strategy in fostering tahfiz motivation, especially for those without a pesantren background. This research makes an initial contribution to the development of Living Qur’an practices in higher education settings focused on tahfiz.